Bone-nerve crosstalk: a new state for neuralizing bone tissue engineering—A mini review - Damiati, Laila A.; El Soury, Marwa (Frontiers in Medicine, 2024)
Neuro bone tissue engineering is a multidisciplinary field that combines both principles of neurobiology and bone tissue engineering to develop innovative strategies for repairing and regenerating injured bone tissues. Despite the fact that regeneration and development are considered two distinct biological processes, yet regeneration can be considered the reactivation of development in later life stages to restore missing tissues.. The skeletal tissue is highly innervated, peripheral nervous system plays a role in conveying the signals and connecting the central nervous system with the peripheral organs, moreover it has been shown that they play an important role in tissue regeneration. Their regeneration role is conveyed by the different cells’ resident in it and in its endoneurium (fibroblasts, microphages, vasculature associated cells, Schwann cells) these cells secrete various growth factors (NGF, BDNF, GDNF, NT-3, and bFGF) that contribute to the regenerative phenotype. The peripheral nervous system and central nervous system synchronize together in regulating bone homeostasis and regeneration through neurogenic factors and neural circuits. Receptors of important central nervous system peptides such as Serotonin, Leptin, Semaphorins and BDNF are expressed in bone tissue playing a role in bone homeostasis, metabolism and regeneration, This review will highlight the crosstalk between peripheral nerves and bone in the developmental stages as well as in regeneration and different neuralized bone tissue engineering strategies for repairing severe bone injuries. For a better understanding of the role of central nervous system role in bone tissue please consult the following reviews [1]–[5].